E-NETWORK SOCIETY: KOMUNALITAS WARGA DALAM KONTEKS SMART CITY - Ahmad Fuadillah Sam (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2018)
Smart city is an informational society’s product through which the society considers that information as a main form to build relations. In this context, smart city becomes an infrastructure that supports network society to work. This article aims to describe smart city’s implication towards the emergence of communality in the city. This study used a qualitative method, through in-dept interviews with related stakeholders to exploring relevant and important data and information about citizens’ communalism produced by Jakarta Smart City Program. Recent studies show theoretical debates about roles and implications of smart city on citizen’s trust towards the government mediated by the technology. This article offers an optimism views concerning smart city as the way the network society manifests through a form of communalities within virtual community. This study shows the ways smart city regulation facilitated by state provides a space for information production by citizens hence communalism built in citizens context. City Communality, in fact could be build within network society mechanism brought by government infrastructure within smart city form. Keywords: Network Society, Smart City, Virtual Community, City Communality, Jakarta Smart City